Resilience of family caregivers of elderly with Alzheimer - Manzini, Carlene Souza Silva (2016)
Resilience is the capacity that people have to cope positively with adversities. A cross-sectional, quantitative study, that aimed to assess factors associated with the resilience of family caregivers of elderly with Alzheimer’s disease. Sixty-six caregivers composed the sample, who were accompanied in a neurology ambulatory. Most caregivers presented moderate resilience. Linear regression showed that some factors interfered with caregivers’ resilience, being those: overload, the increment of days dedicated to caregiving, the level of kinship daughter-in-law/son-in-law or spouse, and practice of other activities besides caregiving. The findings can be useful in care-related areas, once we identified variables interfering in resilience, and those can be worked and improved to benefit the caregiver and the patient.